2015
DOI: 10.1136/bcr-2015-211720
|View full text |Cite
|
Sign up to set email alerts
|

Postsplenectomy thrombocytosis with pseudohyperkalaemia

Abstract: SUMMARYA 52-year old man developed hyperkalaemia on the 11th postoperative day following an extensive open retroperitoneal liposarcoma resection that included splenectomy. Despite thorough investigations, no aetiology for the hyperkalaemia was identified and standard empirical treatment was ineffective. On reconsideration, in view of the patient's concurrent thrombocytosis, a pseudofactual or artefactual hyperkalaemia was suspected. This was confirmed by contemporaneous testing of serum and plasma potassium le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The immunological, hematological and anatomical consequences of splenectomy have long been a source of interest and controversy among researchers and doctors alike [6,9]. Thus, the literature review offers a long array of studies on the complications following the procedure [10,11,12,13,14,15,16]. While attempts to investigate the predictive factors that lead to these complications have been made, we feel confident that enlarging the area of research with a more thorough statistical analysis could greatly benefit patient care [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The immunological, hematological and anatomical consequences of splenectomy have long been a source of interest and controversy among researchers and doctors alike [6,9]. Thus, the literature review offers a long array of studies on the complications following the procedure [10,11,12,13,14,15,16]. While attempts to investigate the predictive factors that lead to these complications have been made, we feel confident that enlarging the area of research with a more thorough statistical analysis could greatly benefit patient care [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to the lack of anticoagulants, the platelets are degranulated, and the intracellular potassium is released. 11 …”
Section: Discussionmentioning
confidence: 99%
“…( 7 ) Pseudohyperkalaemia is also characterised by the absence of ECG changes and symptoms of hyperkalaemia together with a lack of response to the classical treatment of hyperkalaemia. Furthermore, it has been demonstrated that patients with pseudohyperkalaemia secondary to thrombocytosis occur at platelet concentrations above 600 × 10 9 /L ( 8 ). Figure 1 shows that hyperkalaemia occurred when measuring potassium in platelet concentrations >600 × 10 9 /L, even in our limited data set in this single patient.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregates degranulate in these blood samples and release intracellular potassium. ( 8 ) In thrombocytosis, there are more platelets that release more intracellular potassium. Plasma electrolytes are taken in a specialised lithium heparinised bottle where tube inversions ensure mixing of anticoagulant (heparin) with blood to prevent clotting.…”
Section: Discussionmentioning
confidence: 99%